(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Wheat has been considered as the most important cereal after rice in India, contributing 1/3rd to total food nourishment. To feed the expanding population, there need to be increase in production of wheat. Expansion of land to increase the area under wheat is not possible. Development of land to build the zone under wheat is beyond the realm of imagination hence, production can be increased by higher productivity per unit land. Unseemly administration of nutrients causes poor yield of wheat in India. The most conventional way of applying fertilizers by farmers based on blanket recommendation, which does not examine the spatial and temporal variability of nutrients inside the field. In this way there is needed to adopt precision executive practices of nutrient supplements in wheat according to the crop demand and fluctuation within the field. Precision nutrient management helps in increasing yield and also the nutrient recovery as they are applied according to crop demand. Several tools are available for precise application of such as Leaf colour chart, optical sensor (Green Seeker), chlorophyll meter (SPAD), decision support system etc. The point specific nutrient availability also helps in protecting the environment by reducing the emission of harmful gases like N2O.